Estudio Doctrinario del Control Concreto de Constitucionalidad en el Ordenamiento Jurídico Ecuatoriano. - Guachizaca Peralta, Santiago Fabián (2021)
This legal research project includes the theoretical, legal, critical and doctrinal study regarding a subject of constitutional relevance within the country, and whose legal– philosophical trend has been growing exponentially in Latin America, it is specifically about the CONCRETE CONTROL OF CONSTITUTIONALITY collected by the New Constitution of the Republic as a mechanism of constitutional rank for the full development of constitutional rights and the protection of the Magna Carta. The importance of the research is reflected, its academic purpose being to actively contribute to the study of the New Constitutional Control System that arises as a result of the issuance of the Constitution of the Republic of 2008 with its important and radical transition from a Legal State of Rights to a Constitutional State of Rights and Justice, the most important constitutional event of the last decade within Ecuadorian Law, where the Concrete Control of Constitutional Law and the Principle of Constitutional Supremacy are made positive, so that knowing these categories correctly will determine their direct applicability in judicial processes. The purpose of this thesis is to analyze the new legal–constitutional institution established as "CONCRETE CONTROL OF CONSTITUTIONALITY", occupying a preponderant stage within the justiciability of fundamental rights where, without a doubt, its categorical imperative will be necessary and fundamental within the new constitutional systematization of the Ecuadorian Legislation.